The influence of migration policies in Europe on return migration to Senegal - Flahaux, M (International Migration Institute, 2014)
Over the past decade, return migration has generated increasing policy and public attention. It is often believed that African migrants travel to destination countries and generally do not return home. Policy makers in European countries have adopted policies designed to encourage or force African migrants to return. European countries have also designed policies intended to control access and stay of migrants in their territory. These policies have become increasingly restrictive over time towards most categories of African migrants, and they are sometimes invoked to explain the reluctance of migrants to return, since they prevent circulation. Due to the lack of data however, the influence of the different migration policies on return migration remains poorly understood. This paper aims to fill this gap by analysing transnational and biographical data of the Migration between Africa and Europe (MAFE) surveys as well as data of the DEMIG POLICY and DEMIG VISA databases, which cover major changes in migration policies across a large range of destination countries. I implement event history logistic regressions to study the effect of migration policies on the return of Senegalese who migrated to France, Italy and Spain between 1960 and 2008. The results reveal that the policies aiming at controlling the stay and encouraging or forcing the return of migrants do not significantly affect return, but that Senegalese migrants are less likely to return when the entry restrictions have become important. This suggests that barriers intended to reduce the flow of African migrants actually prevent those who are already in Europe from returning. The results show that the preoccupation of migrants is not only the return, but also the possibility of a new migration after the return.